Transition from microstructures to nanostructures and ultimate hardening - Firstov, S.A.; Rogul, T.G.; Shut, O.A. (Functional Materials, 2009)
Regularities of change in the dependence of the yield stress on grain size in transition from the microstructured to the nanostructured state are discussed. It is shown that, using S-functions, a generalized equation for the yield strength dependence on the grain size with regard to changes in the hardening mechanisms of polycrystals in the vicinity of critical grain sizes dcr₁ and dcr₂ can be obtained. This equation enables to describe the softening effects in transition to nanostructures (the so-called "negative" trend of the Hall-Petch relationship) and an abrupt hardening under conditions of increased intergranular cohesive strength. Обговорюються закономірності зміни залежності напруги плинності при переході від мікро- до наноструктурованого стану. Показано, що за допомогою 8-функцій можна отримати узагальнене рівняння залежності границі плинності від розміру зерна з урахуванням зміни механізмів зміцнення полікристалів в околі критичних розмірів зерен dкр₁ і dкр₂. Це рівняння дозволяє описати як ефекти знеміцнення при переході до наноструктур (так званий "негативний" хід залежності Холла-Петча), так і, навпаки, різке зміцнення за умови підвищеної міцності межзеренного зчеплення. Обсуждаются закономерности изменения зависимости напряжения течения при переходе от микро- к наноструктурированному состоянию. Показано, что с помощью 8-функций можно получить обобщенное уравнение зависимости предела текучести от размера зерна с учетом изменения механизмов упрочнения поликристаллов в окрестности критических размеров зерен dкр₁ и dкр₂. Это уравнение позволяет описать как эффекты разупрочнения при переходе к наноструктурам (так называемый "отрицательный" ход зависимости Холла-Петча), так и, напротив, резкое упрочнение при условии повышенной прочности межзеренного сцепления.